A mixed-methods approach to understanding water use and water infrastructure in a schistosomiasis-endemic community: case study of Asamama, Ghana. - Kosinski, Karen Claire.; Kulinkina, Alexandra V.; Abrah, Akua Frimpomaa.; Adjei, Michael N.; Breen, Kara Marie.; Chaudhry, Hafsa Myedah.; Nevin, Paul E.; Warner, Suzanne H.; Tendulkar, Shalini Ahuja. (2016)
Background: Surface water contaminated with human waste may transmit urogenital schistosomiasis (UGS). Water-related activities that allow skin exposure place people at risk, but public health practitioners know little about why some communities with access to improved water infrastructure have substantial surface water contact with infectious water bodies. Community-based mixed-methods research can provide critical information about water use and water infrastructure improvements.; Keywords: Water infrastructure, River, Mixed-methods, Borehole, Improved water source, Surface water, Schistosoma haematobium, Urogenital schistosomiasis.; Springer Open.